Evaluation of objective and subjective clinical outcomes in combat veterans with and without mild TBI and PTSD: A four-group design. Issue 7 (9th August 2019) - Merritt, Victoria C.; Jurick, Sarah M.; Crocker, Laura D.; Hoffman, Samantha N.; Keller, Amber V.; DeFord, Nicole; Jak, Amy J.
ABSTRACT: Introduction : Mild traumatic brain injury (mTBI) and posttraumatic stress disorder (PTSD) are highly prevalent comorbid conditions in military Veterans. However, lack of appropriate comparison groups has clouded interpretation of the chronic effects of these conditions. The present study evaluated the neuropsychological, psychiatric/neurobehavioral, and functional outcomes associated with mTBI and PTSD in a well-characterized sample of combat-exposed Veterans. Method : Participants included 73 Iraq/Afghanistan Veterans (91.8% male; age: M = 34.00, SD = 6.39) divided into four groups: mTBI-only ( n = 23), PTSD-only ( n = 14), comorbid mTBI + PTSD ( n = 19), and combat-control (CC; n = 17). Participants were administered a neuropsychological assessment and completed questionnaires assessing psychiatric/neurobehavioral symptoms and functional outcomes. Results : Kruskal-Wallis H- tests showed no group differences across measures of neuropsychological functioning; however, there were significant differences across groups on all psychiatric/neurobehavioral variables examined. In general, the comorbid and PTSD-only groups endorsed the most severe symptoms, followed by the mTBI-only and CC groups, respectively. As for functional outcomes, the comorbid and PTSD-only groups had higher rates of service-connection disability and greater perceived decline in work and education-related abilities, relative to the mTBI-only and CC groups, despite similar proportions of Veterans employed or in school in each group. Conclusions : Findings suggest that Veterans with comorbid mTBI + PTSD and PTSD alone are at greatest risk for experiencing long-lasting subjective distress, including negative perceptions of their ability to work or pursue an education, despite being comparable to mTBI-only and CC Veterans on objective measures of functioning. Our results highlight the importance of emphasizing mental health treatment in this population.